Sosialiasasi Pemanfaatan Limbah Lidi Kelapa Sawit Menjadi Inovasi Kerajinan Bernilai Jual Bagi Masyarakat di Desa Makmur Kecamatan Sei Lepan Kabupaten Langkat - Yaumul Khair Afif; Syahrul Affan; Muhmmad Renaldi; Muhmmad Hidayat Lubis (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
Makmur Village has a very large area of ​​oil palm plantations. The amount of waste generated by the community's oil palm plantations is comparable to the area of ​​the oil palm plantation, especially the waste of sticks from the fronds of the palm trees. There is still a lot of palm oil waste that has not been utilized and is wasted or broken down by burning it. The purpose of this activity is to utilize palm oil waste to become a valuable product. Products from palm sticks are in the form of plates. Utilizers of palm oil waste can produce woven products that have selling value, are creative and innovative, so that they can improve. The results of observations on the use of palm oil stick waste have begun to be processed into plates. However, craftsmen need to increase their understanding in stages of product technology development and marketing development so that palm oil stick waste craftsmen can improve the economy and create jobs.